The Role of the Agency of Women’s Empowerment, Child Protection, and Family Planning West Java Province in Reducing Violence Against Women - Joeliaty; Marthalina Pulungan; Muhammad Rahimi Hasan (Institut Pemerintahan Dalam Negeri, 2025)
Violence against women in West Java Province continues to increase, placing this region as the province with the highest number of cases nationally, so an analysis of the effectiveness of government efforts in addressing it is necessary. This study aims to identify and explain the role of the Women’s Empowerment, Child Protection, and Family Planning Agency West Jawa Province (DP3AKB) in reducing violence against women through an organizational perspective. The study used qualitative methods with analysis of research documents, SIMFONI-PPA statistical data, and documented structured interviews. The results show that victim protection services, regulatory strengthening, and women's economic empowerment programs such as Sekoper Cinta and WJWE Caang contribute to increasing women's capacity and reducing vulnerability to violence, although their effectiveness is still hampered by limited human resources, disparities in services between regions, and high economic dependence of victims. The study concludes that DP3AKB plays a significant role in efforts to reduce violence, but requires institutional strengthening and multi-sectoral collaboration for more optimal interventions